UJI KEPRAKTISAN LKPD MATERI SISTEM PENCERNAAN BERBASIS PROBLEM BASED LEARNING KELAS XI SMA (Jurnal Biogenerasi, 2026)
This study was motivated by the low level of student engagement in biology learning, particularly in the digestive system topic, and the limited availability of engaging and understandable teaching materials. This research aimed to determine the readability and practicality of Student Worksheets based on Problem Based Learning (PBL) for eleventh-grade senior high school students. The research employed a qualitative descriptive approach and was conducted at SMA Negeri 3 Padang during the first semester of the 2025/2026 academic year. Data were collected through student readability questionnaires and teacher practicality questionnaires using a Likert scale. The results showed that the readability level of the worksheets reached an average score of 84.03%, categorized as very good. Meanwhile, the practicality level based on teacher responses reached an average of 92.29%, categorized as highly practical. These findings indicate that PBL-based worksheets are easy to use, attractive, and capable of supporting student activity and understanding in learning the digestive system. Therefore, the developed worksheets are appropriate to be used as supporting teaching materials in senior high school biology learning.
Keywords: student worksheet, Problem Based Learning; digestive system; readability; practicality